The link between microglia and the severity of COVID‐19: The "two‐hit" hypothesis. Issue 7 (14th April 2021) - Bouayed, Jaouad; Bohn, Torsten
Highlights: Neurological manifestations constitute a serious cause of severe coronavirus disease 2019 (COVID‐19). Microglial hyperactivation by the two‐hit process. Severe COVID‐19 patients carry pre‐activated microglia following a first immune challenge. Exaggerated response of sensitized microglia to COVID‐19, the second immune challenge.